New Analysis of 2ν1 + ν2, ν1 + ν2 + ν3, and ν2 + 2ν3 Bands of Ozone in the 2600-2900 cm−1 Region; Journal of Molecular Spectroscopy; № 33 - Mikhailenko S. N. Semen Nikolaevich; Barbe A.; Plateaux J. J.; Tyuterev Vl. G. (1999, 1999)
Title screen